Компенсація запізнення в контурі керування процесом нанесення ізоляції на струмопровідну жилу кабелю - Островерхов, Микола Якович; Сільвестров, Антон Миколайович; Боряк, Богдан Радиславович (НТУ "ХПІ", 2017)
З метою підвищення якості процесу нанесення полімерної ізоляції на струмопровідну жилу кабелів надвисокої напруги, розглянуто можливість використання в контурі керування технологічним процесом адаптивних до гетероскедастичних збурень фільтрів, функціональні блоки яких - екстраполятори Р. Брауна, що працюють по принципу потрійного експоненціального згладжування, підключені за ноніусним принципом і виконують функції компенсаторів транспортного запізнення. Алгоритм адаптації даного фільтра передбачає використання двох фільтруючих контурів, що функціонують за одним принципом, але із різними параметрами.

To improve quality of the polymer insulation winding process for extra high voltage cables we researched the possibility of using adaptive filter. This filter can be integrated into control system as data processing algorithm and its main aim is to compensate heteroscedastic noise. The working principle is based on double exponential smoothing that was proposed by R. Brown. The lag of triple exponentials moothing was compensated by nonius connection of three filters. In such case filter can be used as a transport delay compensator as well. Algorithm of adaptation was designed to get an ability to change the smoothing factor of the filter during the process. The variability of smoothing factor makes the filter to adapt to changes of noise level and to avoid loss of information. The adaptation process requires using two filtering contours that works with the same principle but with different smoothing factors.
Delay compensation in the control circuit for the insulation process on the conductor cable
Keywords: фільтр-екстраполятор; виробництво кабелів; прогнозування; адаптація; астатизм; експоненціальне згладжування; filter-extrapolator; cable production; exponential smoothing